Effectiveness and safety of dupilumab in adults with moderate and severe atopic dermatitis in Colombia: Real-life experience (2023)
ABSTRACT: Background: Dupilumab is a treatment approved for uncontrolled moderate-to-severe atopic dermatitis (AD). Tropical and developing countries such as Colombia have characteristics that may impact the natural history of AD and access to medical treatments. In that sense, we aimed to describe the effectiveness and safety of dupilumab in adults with moderate to severe AD in a Colombian multicenter cohort. Methods: Multicenter descriptive study that included patients who started treatment between March 2018 and May 2020 in 6 centers. Disease severity was assessed using the following: Scoring Atopic Dermatitis (SCORAD), Eczema Area and Severity Index (EASI), Patient Oriented Eczema Measure (POEM), and Dermatology Life Quality Index (DLQI). These measurements were collected according to availability at baseline, 3-5 months, 6-12 months, and more than 12 months. Days of sick leave, hospitalizations, and AD flares before and after dupilumab treatment were reported. Adverse events (AEs) were recorded during follow-up. Results: Ninety-three patients were included, with a median age of 32 years (IQR: 24.0; 40.0) and a disease evolution time of 21 years (IQR: 16.0; 29.5). 88.2% had at least 1 allergic disease other than AD. An improvement greater than or equal to 75% EASI was observed in 41.7% of patients at 3-5 months, in 73.7% of patients at 6-12 months, and in 75.0% of patients after 12 months. For those reporting SCORAD and POEM, the median percent change ([IQR], n) from baseline in SCORAD was -67.1 ([-79.2; -54.2], n = 16), -70.5 ([-85.8; -47.9], n = 36) and -66.7 ([-77.3; -51.0], n = 13); and POEM, -58.6 ([-66.4; -55.5], n = 4), -73.0 ([-86.5; -66.7], n = 16) and -87.3 ([-93.4; -69.6], n = 8), respectively. Before initiation of dupilumab treatment, 82 (88.2%) patients reported at least 1 flare of AD in the past 12 months. During the follow-up period, 30 (32.3%) patients reported at least 1 exacerbation or flare. Twelve patients (12.9%) presented an AE and 3 (3.2%) patients discontinued dupilumab for this cause. Conclusions: Dupilumab was effective and safe for the treatment of moderate to severe AD in point-of-care settings, with results similar to randomized controlled and other real-life studies. These positive results are still maintained even though a high number of patients had short interruptions in the use of dupilumab due to administrative problems.